2021
DOI: 10.1002/pc.26327
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of piezoresistive flexible pressure sensors based on poly(vinylidene fluoride)/thermoplastic polyurethane filled with carbon black‐polypyrrole

Abstract: Electrically conductive composites of thermoplastic polyurethane (TPU), poly(vinylidene fluoride) (PVDF), and carbon black-polypyrrole (CB-PPy) were prepared by melt compounding followed by compression molding or by filament production followed by fused filament fabrication (FFF). The storage modulus (G 0 ) and complex viscosity (η*) of the composites increased with the addition of CB-PPy leading to a more rigid material. The electrical and rheological percolation threshold of composites were 5 and 3 wt%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…The piezoresistive flexible sensor printed by Bertolini et al for CB reinforced PMCs has high sensitivity and high measurement factor values, large pressure range and repeatable piezoresistive response over 100 cycles. 143 Manganiello et al 144 tried to use CB to fill TPU and printed displacement sensors with the FDM printing process, successfully verifying the possibility of fabricating displacement sensors with this composite material. While Yang et al 145 printed photoresponsive shape memory devices with CB/TPU composites, as shown in Figure 6B.…”
Section: Applications Of Cb-reinforced Pmcsmentioning
confidence: 98%
See 1 more Smart Citation
“…The piezoresistive flexible sensor printed by Bertolini et al for CB reinforced PMCs has high sensitivity and high measurement factor values, large pressure range and repeatable piezoresistive response over 100 cycles. 143 Manganiello et al 144 tried to use CB to fill TPU and printed displacement sensors with the FDM printing process, successfully verifying the possibility of fabricating displacement sensors with this composite material. While Yang et al 145 printed photoresponsive shape memory devices with CB/TPU composites, as shown in Figure 6B.…”
Section: Applications Of Cb-reinforced Pmcsmentioning
confidence: 98%
“…Loh et al 142 made CB/TPU electrodes and TPU insulators with a multi‐material FDM printer and developed a metamaterial capacitive sensor array with a 6 × 6 sensor to detect the clamping forces of fixture and the normal forces on bending deformation surfaces of the human elbow(Figure 6A). The piezoresistive flexible sensor printed by Bertolini et al for CB reinforced PMCs has high sensitivity and high measurement factor values, large pressure range and repeatable piezoresistive response over 100 cycles 143 . Manganiello et al 144 tried to use CB to fill TPU and printed displacement sensors with the FDM printing process, successfully verifying the possibility of fabricating displacement sensors with this composite material.…”
Section: Carbon‐reinforced Pmcs and Their Applicationsmentioning
confidence: 99%
“…As per recent studies, the uncertainty of the self-heating error is lesser when the twocurrent ratio is 1:2. [35] Therefore electrical current ratio chosen in this study for the evaluation of R 0,two-currents for several pairs of resistance values were (0.5,1), (1,2), (2,4), (2.5,5), and (3,6) mA. The self-heating error was then calculated using the average, R 0,average , of the different R 0,two-currents values obtained for each pair of selected electrical currents.…”
Section: Self-heating Analysismentioning
confidence: 99%
“…Polymer-based nanocomposites have exhibited great potential in the field of flexible sensors. [1][2][3][4] A flexible temperature sensor has two major components: the thermo-sensitive element whose electrical signal changes due to the temperature change and the flexible substrate (mostly polymeric) that adheres conformably strictly to the surface area whose temperature is to be measured. Compatible fillers, when used in appropriate concentration can bring significant changes in the sensor's performance.…”
Section: Introductionmentioning
confidence: 99%
“…6,28,29 Previous researches showed that hybrid materials of PVDF and TPU offers unique advantages of mechanical properties, such as stretchability and flexibility, and pyroelectric/piezoelectric properties. 4,6,[28][29][30][31] Furthermore, the dispersion of nanofillers is an interesting strategy to induce the formation of an electroactive phase and enhance piezoelectric properties of PVDF. 5,10,12,13,16,20,21,23,25,32 Among the reported nanofillers, carbon nanofillers have been mostly used because of their high surface area, good mechanical properties, elevated electron transport properties, and superior polymer-filler interfacial interactions.…”
Section: Introductionmentioning
confidence: 99%